Molecular profiling of basal cell carcinoma of the prostate: A case report and literature review - Luca Bertozzi; Eileen Zhang; Mohadese Behtaj; Olivia Gordon; Yuan James Rao; Michael J. Whalen (Urology Case Reports)
Prostate basal cell carcinoma (BCC) is a rare pathologic variant with a poorly understood molecular profile. Here, we describe a case of prostate BCC and compare its genetic alterations to cases in the literature. After presenting with hematuria, our patient underwent definitive radical prostatectomy for his localized biopsy-proven BCC. Somatic and germline testing revealed mutations in PIK3R1, KMT2D, and NOTCH1, and MUTYH, NBN, and MSH3, respectively. Upon literature review, we found that prostate BCC mutations disrupt cell growth, epigenetic regulation, and cell fate determination. With no consensus guidelines available, experimental targeted therapies have shown promise for prostate BCC management.